Reinterpretasi Biaya Operasional Ritual Kematian demi Keberlanjutan Pendidikan Generasi Muda - Mohammad Zakki (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Rituals for the dead are sacred activities that have become an Islamic tradition among society, especially in the Madura region. The operation of this ritual requires large costs that must be paid by the family regardless of economic class. This tradition, in another paradigm, has an impact on the continuity of education for the family of the deceased. This research was carried out in Tamberru Laok Sokobenah Sampang Village using qualitative research and a phenomenological approach. Techniques for collecting data using participant observation, in-depth interviews and documentation. The results of this research: the death ritual event is an Islamic tradition that continues from previous elders with the aim of adding goodness to the deceased, this activity costs quite a lot of money which becomes a burden for the family, the alternative to operational costs is going into debt and/or mortgaging the land which has an impact on the majority Every family migrates abroad, the source of funding comes from agreements and solidarity built within the family, and the biggest impact is the family's low level of attention to the education of the younger generation.